Implementation of School Culture-Based Character Education Strengthening Program at SMP Negeri 10 Satap Tondano - Mangare, Alfando Cester; Langkai, Jeane Elisabeth; Tuerah, Paulus Robert (Technium Social Sciences Journal, 2023)
This study aims to analyze the implementation of the school culture-based Character Education Strengthening (PPK) program at SMP Negeri 10 Satap Tondano. This research uses a qualitative approach. Data collection in this study was carried out using in-depth interviews, observations, and documentation studies. The results of this study show that the implementation of the school culture-based Character Education Strengthening Program (PPK) at SMP Negeri 10 Satap Tondano has not been implemented optimally due to: 1) the availability of inadequate school facilities and infrastructure to support extracurricular and co-curricular activities which are mandatory components in the implementation of school culture-based KDP, 2) parental support for the child's education process that is still lacking, and 3) inadequate school financing in financing the implementation of activities and the procurement of school facilities and infrastructure. For this reason, we should: 1) schools need to coordinate with all stakeholders in the field of education, 2) the government needs to provide sufficient funds to support the implementation of school-based KDP, 3) need maximum support from parents in the form of attention and supervision of children's associations.